P‐Wave Amplitude and PR Changes in Patients With Inappropriate Sinus Tachycardia: Findings Supportive of a Central Mechanism. Issue 9 (13 September 0207) - Field, Michael E.; Donateo, Paolo; Bottoni, Nicola; Iori, Matteo; Brignole, Michele; Kipp, Ryan T.; Kopp, Douglas E.; Leal, Miguel A.; Eckhardt, Lee L.; Wright, Jennifer M.; Walsh, Kathleen E.; Page, Richard L.; et al.
Abstract : Background: The mechanism of inappropriate sinus tachycardia (IST) remains incompletely understood. Methods and Results: We prospectively compared 3 patient groups: 11 patients with IST (IST Group), 9 control patients administered isoproterenol (Isuprel Group), and 15 patients with cristae terminalis atrial tachycardia (AT Group). P‐wave amplitude in lead II and PR interval were measured at a lower and higher heart rate (HR1 and HR2, respectively). P‐wave amplitude increased significantly with the increase in HR in the IST Group (0.16±0.07 mV at HR1=97±12 beats per minute versus 0.21±0.08 mV at HR2=135±21 beats per minute, P =0.001). The average increase in P‐wave amplitude in the IST Group was similar to the Isuprel Group ( P =0.26). PR interval significantly shortened with the increases in HR in the IST Group (146±15 ms at HR1 versus 128±16 ms at HR2, P <0.001). A similar decrease in the PR interval was noted in the Isuprel Group ( P =0.6). In contrast, patients in the atrial tachycardia Group experienced PR lengthening during atrial tachycardia when compared with baseline normal sinus rhythm (153±25 ms at HR1=78±17 beats per minute versus 179±29 ms at HR2=140±28 beats per minute, P <0.01). Conclusions: We have shown that HR increases in patients with IST were associated with an increase in P‐wave amplitude in lead II and PR shortening similar to what is seen in healthy controls following isoproterenol infusion. The increase in P‐wave amplitude and absence of PR lengthening in IST support an extrinsic mechanism consistent with a state of sympatho‐excitation with cephalic shift in sinus node activation and enhanced atrioventricular nodal conduction.